Trauma‑related Hallucination in an 8‑year‑old Child with Dissociative Symptoms - Nathratul Ayeshah Zulkifli; Aliyyah Mohammad Khuzaini; Abdul Rasyid Abdul Aziz; Hamidin Awang (Wolters Kluwer - Medknow, 2024)
Malaysian Journal of Psychiatry Volume: 32 No: 2 (page: 85-90)